Reliability Enhancement Test of DTECS-2 - WANG Peng; HUANG Cheng; XU Lifeng; LIU Guotao; SHI Li (机车电传动)
Against the current status that rail transit field had no reliability enhancement test standards, by analyzing the workingenvironment, the main stress to influence DTECS-2 reliability was determined. Reliability enhancement test scheme with temperaturestep stress test (low temperature stepping, high temperature stepping), rapid temperature cycling test, vibration step stress test andcomprehensive stress test was designed. The test triggered 34 kinds of product failure modes, and with analysis and modification, greatlyimproved the inherent reliability of the product.